Electronic Declaration of Assets as a Way to Prevent Corruption - A. A. Nurkey; A. B. Kosherbayeva; N. K. Kuandykov (Экономика: стратегия и практика, 2022)
The asset declaration contains valuable information to help uncover misconduct and illicit enrichment and to ensure that managers are held accountable, and their assets are not acquired through corruption. In general, the use of the electronic type of income declaration has a positive effect on combating corruption. Nevertheless, having numerous positive features, this species also contains a number of disadvantages and difficulties. Many states and international organizations are introducing declarations of income and assets to reduce the level of the shadow economy. As a result, it was revealed that in the states where the practice of declaring income and assets was introduced in the early period, the level of corruption crimes has been reduced. However, there is still debate about the adoption of this mechanism as an anti-corruption tool. This article examines not only the work of researchers in the field of declaring and combating corruption but also international research, the experience of which can also be used in Kazakhstan. This article examines the effectiveness of using the declaration of income and assets, including universal declaration, through electronic media to combat corruption. For the analysis, a SWOT analysis was selected, through which the main key points were assessed and recommendations were developed, especially for the Kazakhstan anti-corruption policy. The result of this analysis showed that the implementation of universal declaration through electronic resources is certainly an effective activity, but costs and challenges, such as cybersecurity, streamlining of business management processes, technical errors, and system failures, must also be taken into account.